RISK MANAGEMENT AND BANKING PERFORMANCE WITH CORPORATE GOVERNANCE AS MODERATING VARIABLE - Hikmawati, Santi; Sutrisno, Sutrisno (Buletin Studi Ekonomi, 2021)
This research aims to analyze the effect of risk management on bank financial performance with corporate governance as a moderating variable. The independent variables used in this research are risk management, consist of credit risk (NPL), liquidity risk (LDR), and operating risk (OEIR). The dependent variable used is financial performance (ROA). Meanwhile, corporate governance as a moderating variable and firm size as a control variable. The regression model used are multiple linear regression analysis and moderated regression analysis. The sample was selected through purposive sampling method and 43 banks were selected as research sample. The result of this research showed that NPL and OEIR have a negative and significant impact on financial performance. Meanwhile, LDR has not significant effect on financial performance. Corporate governance was able to moderate the relationship between NPL and OEIR on financial performance, but unable to moderate the relationship between LDR on financial performance.